OPTIMIZATION OF 3D PRINTING PARAMETERS FOR PLA/PCL FILAMENT USING THE TAGUCHI METHOD: EFFECTS ON MECHANICAL PROPERTIES AND SHAPE MEMORY PERFORMANCE - Eryildiz, Meltem; Utluhan, Bekir Kagan; Altan, Mihriguel Eksi (Konya Teknik Univ, 2025)
This study investigates the optimization of 3D printing process parameters for PLA/PCL filament using the Taguchi method. A Taguchi L9 orthogonal array design was employed to explore the effects of print speed (40, 60, 80 mm/s), temperature (185,190,200 degrees C), and infill pattern (the Lines, Gyroid, Triangle) on both mechanical and shape memory properties of the printed parts. The experiments were conducted using a Fused Deposition Modeling (FDM) 3D printer. The mechanical properties, including tensile strength, and shape memory properties such as shape recovery ratio, were evaluated for each combination of process parameters. The experiments revealed that a print speed of 40 mm/s, a nozzle temperature of 185 degrees C, and the Lines infill pattern produced the best shape memory performance, achieving the shape recovery rate of 78.60% and the recovery time of 69 seconds. For tensile strength, the optimal conditions were found to be 40 mm/s, 185 degrees C, and the Gyroid infill pattern, resulting in the highest tensile strength of 21.985 MPa. However, for simplicity and faster production, the Lines infill pattern is preferred. This research provides valuable insights for optimizing the 3D printing process of PLA/PCL filament and enhancing its mechanical and shape memory performance, which is crucial for various applications in biomedical, textile, and packaging industries.
Keywords: 3D Printing; Mechanical Properties; PLA/PCL Filament; Shape Memory Properties; Taguchi Method; Engineering